Book Review: Experimental Archaeology and Fire. The Investigation of a Burnt Reconstruction at West Stow Anglo-Saxon Village by Jess Tipper - Claudia Speciale (EXARC Journal)
What should an archaeologist do if one of the reconstructions of an experimental village is accidentally burning during the night? Simple: pick up a camera and start taking pictures. And then, of course, plan the excavation to record as much information as possible followed by an analytical and detailed publication on the results.